2013
DOI: 10.4238/2013.november.22.12
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Transient increase in IL-1β, IL-6 and TNF-α gene expression in rat liver exposed to gold nanoparticles

Abstract: ABSTRACT. Most studies have used in vitro systems to test inflammatory responses of nanoparticles; these may not reflect the real biological response of body organs. In fact, certain nanoparticles have provoked opposite effects under in vitro and in vivo conditions. Current understanding of the biocompatibility of gold nanoparticles is controversial. We studied the acute (1 day) and sub-chronic (5 days) effects of gold nanoparticles (10 and 50 nm in diameter) on expression of interleukin-1 beta (IL-1b), IL-6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 23 publications
(25 reference statements)
4
35
0
1
Order By: Relevance
“…Elevated levels of TNF-α and decreased the anti-inflam-matory IL-4 contents in testicular and prostatic tissues are additional evidences of the aggressive cellular inflammatory response to ZnO NP exposure through the current study. Such in vivo increased TNF-α in nanoparticle exposure is in accordance with [41][42][43]. Increased TNF-α, decreased IL-4 and disturbed levels of other inflammation modulatory cytokines on exposure to nanoparticles was reported also by [42,44].…”
Section: The Mean Area % Of Masson Trichrome and Inos Immunoreactiosupporting
confidence: 77%
“…Elevated levels of TNF-α and decreased the anti-inflam-matory IL-4 contents in testicular and prostatic tissues are additional evidences of the aggressive cellular inflammatory response to ZnO NP exposure through the current study. Such in vivo increased TNF-α in nanoparticle exposure is in accordance with [41][42][43]. Increased TNF-α, decreased IL-4 and disturbed levels of other inflammation modulatory cytokines on exposure to nanoparticles was reported also by [42,44].…”
Section: The Mean Area % Of Masson Trichrome and Inos Immunoreactiosupporting
confidence: 77%
“…Parts of liver samples were used to evaluate the Real-time RT-PCR for IL-1β, IL-6 and TNF-α. It was investigated as reported by Kha et al [20]. The primers sequences were IL-1β, forward (5′-CACCTTCTTTTCCTTCATCTTTG-3′) and reverse (5′-GTCGTTGCTTGTCTCTCCTTGTA -3′), IL-6, forward (5′-TGATGGATGCTTCCAAACTG-3′) and reverse (5′-GAGCATTGGAAGTTGGGGTA-3′), TNF-α, forward (5′-ACTGAACTTCGGGGTGATTG -3′) and reverse (5′-GCTTGGTGGTTTGCTACGAC-3′) and GADPH forward (5′-GTATTGGGCGCCTGGT-CACC-3′) and reverse (5′-CGCTCCTGGAAGATGGT-GATGG-3′).…”
Section: Real-time Rt-pcr For Il-1β Il-6 and Tnf-αmentioning
confidence: 99%
“…Gold nanoparticles (10 nm and 50 nm in size) induced IL-1 β , IL-6, and TNF- α in rat liver cells after 1 day of acute treatment and then subsided by day 5 of subchronic treatment. The 50 nm gold nanoparticles produced more severe inflammation than the 10 nm gold nanoparticles [48]. However, limited studies demonstrated whether or which TLR is involved in the NPs induced proinflammatory cytokines production.…”
Section: Nanoparticles and Immune Systemmentioning
confidence: 99%